À bas la République ! Au poteau ! Mort aux juifs ! La violence des graffitis d’extrême droite, de la naissance de l’Action française à Vichy - Richard Vassakos (Cahiers d’histoire)
Under the Third Republic, the urban symbolic system was massively occupied by republican signs, thatformed a veritable symbolic discourse that criss-crossed the space. This appropriation of the territory, as well as the regulation of public signs by the law of 29 July 1881, left little room for those who hated the regime and were relegated to the margins of urban space. The protest then takes on the features of a graphic guerrilla warfare that goes hand in hand with other acts that the authorities qualify as vandalism. It is a cheap way of appropriating space and publicly propagating one's own slogans, slogans and values. Graffiti also proves to be a protean weapon that allows one to confront one's political opponents. From the Dreyfus affair to Vichy, the camelots du roi and, following them, the men of the Leagues or the Doriotists practised agitation by using the weapon of graffiti. They established a dialectical relationship with the republican political power but also with other political factions with whom they fought on the walls.